Witnessing absences: social media as archives and public spheres. (4th May 2017) - Mylonas, Yiannis
ABSTRACT: The study inquires on the ways content-specific social media pages can function as alternative public spheres, by examining the photography-orientated Facebook and YouTube pages entitled 'old photographs of Thessaloniki'. The study focuses on the online encountering of absences, notably events of socio-political importance with a traumatic impact, which were marginalized by historiography and erased from the city's material form. In particular, it looks at the ways these absences are witnessed, remembered and negotiated online, through their formal and informal traces. Departing from Benjamin's and Agamben's theorizations of memory, media and witnessing, and Derrida's work on specters, the study concludes that the pages form a highly informed digital archive in constant development that fosters narratives enhancing cultural toleration and understanding, while challenging official master frames. A class-orientated understanding of the city's 'ruinification' and oblivion is, however, undermined, although it remains in a 'spectral' form.